NLRP12 Attenuates Inflammatory Bone Loss in Experimental Apical Periodontitis. (April 2019) - Taira, T.M.; Lima, V.; Prado, D.S.; Silva, T.A.; Issa, J.P.M.; da Silva, L.A.B.; Zamboni, D.S.; Cunha, F.Q.; Fukada, S.Y.
Apical periodontitis is an inflammatory disorder that results from the host immune response to microbial infection through the dental pulp, leading to alveolar bone destruction. The nod-like receptor 12 (NLRP12) is an atypical intracellular sensor of the NLR family that is involved in the negative regulation of several inflammatory conditions and also osteoclastogenesis. However, the role of NLRP12 in the regulation of immune response and bone loss induced by bacterial infection remains unclear. Here we investigated the development of apical periodontitis in wild-type (WT) and NLRP12 knockout (NLRP12 –/– ) mice by using micro–computed tomography together with histological, immunohistochemical, and molecular analyses. We found that NLRP12 –/– mice are highly susceptible to apical periodontitis induced by bacterial infection, which is associated with an elevated infiltration of neutrophils and macrophages, periapical lesion extension, and alveolar bone destruction. Furthermore, NLRP12 –/– mice showed a high expression of inflammatory cytokines ( Il1b, Il6, and Tnfa ) and the osteoclastogenic markers ( Rankl and Acp5 ) in the periapical tissues. Consistent with this observation, NLRP12 –/– mice showed an increased number of tartrate-resistant acid phosphatase–positive cells lining the apical periodontitis site, which was associated with augmented expression of the osteoclast effector genes, Ctsk and Mmp9 . Mechanistically, NLRP12-deficient preosteoclasts showed elevated IκB-α degradation and p65 phosphorylation when stimulated with receptor activator of nuclear factor (NF)–κB ligand (RANKL). Similarly, increased IκB-α degradation was observed in the periapical tissue of NLRP12 –/– mice. Furthermore, our in vitro study showed that preosteoclasts from NLRP12 –/– mice exhibited higher RANKL-induced osteoclastogenesis, which was synergistically amplified by interleukin-1β and tumor necrosis factor α (mimicking an inflammatory periapical milieu). In conclusion, our data show that NLRP12 exhibits a protective role in the periapical bone destruction by attenuating inflammation and osteoclastogenesis through negative regulation of the NF-κB pathway.